2017
DOI: 10.1371/journal.pone.0190224
|View full text |Cite
|
Sign up to set email alerts
|

Future changes in hydro-climatic extremes in the Upper Indus, Ganges, and Brahmaputra River basins

Abstract: Future hydrological extremes, such as floods and droughts, may pose serious threats for the livelihoods in the upstream domains of the Indus, Ganges, Brahmaputra. For this reason, the impacts of climate change on future hydrological extremes is investigated in these river basins. We use a fully-distributed cryospheric-hydrological model to simulate current and future hydrological fluxes and force the model with an ensemble of 8 downscaled General Circulation Models (GCMs) that are selected from the RCP4.5 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 76 publications
12
141
0
Order By: Relevance
“…Over the coming few decades, discharge in the UIB is expected to increase based on climate model predictions due to a combination of predicted warming enhancing the rate of glacial melt and increases in winter and summer precipitation (Ali et al, 2015;Brun et al, 2017;Immerzeel et al, 2013;Kraaijenbrink et al, 2017;Lutz et al, 2014;Wijngaard et al, 2017). At the subregional level, however, these changes might not be uniform.…”
Section: Discussionmentioning
confidence: 99%
“…Over the coming few decades, discharge in the UIB is expected to increase based on climate model predictions due to a combination of predicted warming enhancing the rate of glacial melt and increases in winter and summer precipitation (Ali et al, 2015;Brun et al, 2017;Immerzeel et al, 2013;Kraaijenbrink et al, 2017;Lutz et al, 2014;Wijngaard et al, 2017). At the subregional level, however, these changes might not be uniform.…”
Section: Discussionmentioning
confidence: 99%
“…The surface water availability is generally largest during the monsoon season (Figure 3c) varying from less than 100 mm/year in the floodplains of the Indus (LIB) to more than 3500 mm/year in the 5 mountainous upstream domains of the Ganges and Brahmaputra. In these domains, the large surface water availability can mainly be attributed to the combined contributions from ice and snowmelt, and monsoon precipitation that can reach amounts over 3000 mm/year at the southern margins of the UGB and UBB (Wijngaard et al, 2017). During the winter season (see Fig 3a) the surface water availability is generally lowest with rates less than 100 mm/year in most regions of the IGB.…”
Section: Blue Water Availabilitymentioning
confidence: 99%
“…The model runs at a spatial resolution of 5 x 5 km and reports on a daily time step. SPHY has been used to assess climate change impacts for high mountain hydrology before (Lutz 25 et al, 2014(Lutz 25 et al, , 2016aWijngaard et al, 2017). The used set up was calibrated and validated using IceSat glacier mass balance data (Kääb et al, 2012), MODIS snow cover data (Hall et al, 2002;Hall and Riggs, 2015) and observed discharge in a study on the impacts of climate change on hydrological extremes in the upstream domains of the IGB (Wijngaard et al, 2017).…”
Section: Upstream: Sphymentioning
confidence: 99%
See 1 more Smart Citation
“…The available data also needs a lot of preprocessing, as it represents uncorrected raw precipitation readings, and, therefore, needs checking for quality issues and correction for losses or gaps. Similarly, while most of the weather stations have become operational after the mid-nineties, long-term data is a rear commodity and only available at a limited number of locations.Owing to the complex orography of the UIB region and to the co-action of different hydro-climatic regimes (which affect the amounts, spatial patterns and the seasonality of precipitation), neither the sparse observed station data (or the gridded data products based on them) nor the sensors-based data, fully represents the precipitation regime of the region [11][12][13][14]. Several studies have pointed out that precipitation in the HKH (Hindu Kush Himalayan) -region exhibits large changes over short distances and has a considerable vertical gradient [15][16][17][18][19][20].…”
mentioning
confidence: 99%